Psychostimulant Use Disorder, an Unmet Therapeutic Goal: Can Modafinil Narrow the Gap? - Hersey, Melinda; Bacon, Amanda K.; Bailey, Lydia G.; Coggiano, Mark A.; Newman, Amy H.; Leggio, Lorenzo; Tanda, Gianluigi (Frontiers in Neuroscience, 2021)
The number of individuals affected by psychostimulant use disorder (PSUD) has increased rapidly over the last few decades resulting in economic, emotional, and physical burdens on our society. Further compounding this issue is the current lack of clinically approved medications to treat this disorder. The dopamine transporter (DAT) is a common target of psychostimulant actions related to misuse and dependence, and the recent availability of atypical DAT inhibitors as a potential therapeutic option has garnered popularity in this research field. Modafinil (MOD), which is approved for clinical use for the treatment of narcolepsy and sleep disorders, blocks DAT just like commonly abused psychostimulants. However, preclinical and clinical studies have shown that it lacks the addictive properties (in both behavioral and neurochemical studies) associated with other abused DAT inhibitors. Clinical availability of MOD has facilitated its off-label use for several psychiatric disorders related to alteration of brain dopamine (DA) systems, including PSUD. In this review, we highlight clinical and preclinical research on MOD and its R-enantiomer, R-MOD, as potential medications for PSUD. Given the complexity of PSUD, we have also reported the effects of MOD on psychostimulant-induced appearance of several symptoms that could intensify the severity of the disease (i.e., sleep disorders and impairment of cognitive functions), besides the potential therapeutic effects of MOD on psychostimulant-induced misuse and dependence.